Radiation-induced Rearrangement of Defects in Silicon Crystals - Pavlyk, B.V.; Lys, R.M.; Hrypa, A.S.; Slobodzyan, D.P.; Khvyshchun, I.O.; Shykoryak, I.A.; Didyk, R.I. (Ukrainian Journal of Physics, 2022)
Physical and mathematical models of the radiation-induced ordering of a defect structure in silicon crystals are proposed. These models involve an increase of the diffusion coefficient of interstitial silicon in the irradiation field and a reduction of the defect lifetime at irradiation doses below 260 Gy. Free surfaces of crystals, phase interfaces, and dislocations are considered to be effective defect sinks.